Botulinum neurotoxin formulations: overcoming the confusion [Corrigendum] - Samizadeh S; De Boulle K (Dove Medical Press, 2018)
Samizadeh S, De Boulle K. Clin Cosmet Investig Dermatol. 2018;11:273–287.On page 273, Introduction section, line 5, the sentence “The human nervous system is susceptible to BoNT-A, B, C, E, F, and G and unaffected by D.1,4–6” should be changed to “The human nervous system is susceptible to BoNT-A, B, C, E, F, and G and almost unaffected by D.1,4–6,131”. On page 273, Introduction section, line 11, “BoNTs” should be changed to “botulinum toxins”. On page 276, Table 2, Storage conditions column, “Below 8°C” should be changed to “2°C–8°C”.  Read the original article